Analysis of Students Mathematical Communication Ability in Solving Trigonometry Problems Reviewed from Students Learning Interests - Faradillah, Ayu (FKIP Universitas Lampung, 2022)
Mathematical communication ability have an important role for students in knowing their abilities when communicating their understanding. The purpose of this study is to analyse students’ mathematical communication ability in solving trigonometry problems in terms of interest in learning. This research uses qualitative descriptive research. The instrument used in this study were the questionnaire interest in learning, the mathematical ability test, and interview. The results of this study is mathematical communication ability is different for every subject both orally or writing related with interest in learning. And the conclusion of the study is mathematical communication ability in writing, subject with high interest learning still better than the subject interested in learning is medium and the interest in learning is low. While the ability to communicate mathematically oral subject with medium and low interest learning still better than the subject interested in learning is high. Keywords: mathematical communication ability, learning interest, trigonometry. DOI: http://dx.doi.org/10.23960/jpmipa/v23i2.pp774-792